Method DestinationIn Delivery of Merchandise (Case Study of Cahaya Ternak Trading Company PS) - Ranelsa Putri; Endah Masrunik; Irvan Ali Mustofa (Jurnal Ilmu Ekonomi dan Sosial (JIES), 2024)
Freight forwading procedures have a significant impact on a company’s operations and profitability. The destination shipping method is used because it allows for lower operational costs and more efficient logistics because the title of the product passes from the supplier to the buyer upon arrival at the destination. This research aims to find out how to apply the destination method in acquiring trade goods at Cahaya Ternak Ps. This research uses qualitative description with interviews and documents related to purchasing procedures at Cahaya Ternak Ps are used to collect data. The results showed that Cahaya Ternak Ps can gain several benefits by using the destination approach, including reduced operational costs and improved inventory control. This approach also lowers the likelihood of damaged goods, guaratees timely delivery of goods, and improves operational effectiveness. This approach is essential fo maintaining the supply and quality of animal feed products, as seen from the regularity of purchases made throughout the year.